Application of Cytokinin and Mycorrhiza to Increase Production and Quality of Pineapple Seedlings from Crown Leaf Bud Cuttings - Putri, Dirgahani; Suhartanto, M. Rahmad; Widajati, Eny (Journal of Tropical Crop Science, 2020)
The pineapple vegetative propagation method using crown leaf bud cuttings has potential to produce seedlings of greater uniformity and in larger quantities than other methods. This study, aimed to explore the potential eff ects of concentration and frequency of Benzylaminopurine (BAP) application for increasing the production and quality of pineapple seedlings from crown leaf bud cutting propagation. The experiment used a randomized complete block design (RCBD) with two factors. The fi rst factor was the concentration of BAP (0, 200, 400, 600, 800 ppm) and the second factor was the frequency of BAP application (1, 2, 3 times). Furthermore, this study investigated the eff ects of applying mycorrhizae to accelerate seedling growth and improve seedling quality during production from crown leaf bud cutting propagation. The experiment used a RCBD with one factor (dose of mycorrhiza: 0, 50, 100, 150, 200 spores). The results indicated that the eff ects of concentration and frequency of BAP application and their interaction increased seed production as determined by sprout cuttings at 5 weeks after planting by applying 600 ppm 2 times. Generally, with increasing concentration and frequency of BAP application, leaf chlorophyll content was reduced. However, the application mycorrhiza positively infl uenced the production of seedlings from pineapple crown bud cuttings and improved seedling quality as measured by root dry weight, chlorophyll content, root infection, and phosphatase enzyme activity.